Biomaterials: Synthetic Biology Makes Polymer Materials Count (Adv. Mater. 21/2018). Issue 21 (May 2018) - Beyer, Hannes M.; Engesser, Raphael; Hörner, Maximilian; Koschmieder, Julian; Beyer, Peter; Timmer, Jens; Zurbriggen, Matias D.; Weber, Wilfried
Abstract : Based on synthetic biology‐derived molecular tools and design concepts, in article number1800472, Wilfried Weber and co‐workers present biohybrid material systems that count the number of light pulses and release different output molecules as a function of the number of light pulses detected. Using a quantitative mathematical model, input configurations can efficiently be identified yielding desired system outputs. Cover image designed by Michal Rössler.